Analisis Gaya Bahasa dalam Novel Dengji Karya Zhao Shuli - Andyni Khosasih (Bina Nusantara University, 2010)
This paper discusses the language and style used in Novel entitled “Dengji”, one of the famous novels written by Zhao Shuli. This paper also discusses deeper about the content of the novel, the framework and the characters in the novel. It is found that first, the writer uses simple language and easy to understand. The objective of the writer to use simple language is because it is objected to the farmers with lower level of education. Second, the frame of the novel is clear. Therefore, the readers can easily follow the thought and ideas of the writer. Third, the women characters in this novel are divided into two types. The first type is the ones who keep the feudalism view, and the other is the one who are against the view.